A Journey to Ethical Life: A Moral Reading of Shakespeare’s Othello through the Nasirean Ethics of Naṣir Al-Din Al-Ṭuṣi - Mochammad Dwi Teguh Prasetya; Muh. Arif Rokhman (Universitas Gadjah Mada, 2019)
This research is an attempt of offering a moral reading of Shakespeare’s Othello through The Nasirean Ethics (Akhlaq-i Naṣiri) by Naṣir Al-Din Al-Ṭuṣi. It aims to analyse the ethical life of the characters in it, how virtues and vices of a human soul are being reflected, as well as the social and political life in Othello as reflected by the interaction of its characters. In conducting the research, excerpts from the play are accordingly collected and investigated, and for the primary discussion, the selective materials from The Nasirean Ethics of Al-Ṭuṣi are employed. The result of the research shows that in man’s existence within the universe, cultivating virtue and removing vices are things of most importance. Othello, Iago, and Roderigo are perplexed by the vices of the soul, a quality when the golden mean of virtue is not at equilibrium. In social and political life, the ethical components of justice and love are necessary as well as the presence of law, just arbitrator, and money. This research suggests that the cultivation of morality and ethics should be the ground of every civilization.